Determinants of hospital length of stay in ischemic stroke patients: A retrospective cohort study at Indonesian national stroke center - Mursyid Bustami; Sri Idaiani; Nadira Deanda Putri; Ari Winasti Satyagraha; Novaria Sari Dewi Panjaitan; Anna Mardiana Ritonga; Anyelir Nielya Mutiara Putri; Shofiya Rohmah Asyahida; Mei Sarah Nurkhalizah; Diva Azizah Nitisara; Beny Rilianto; Nugroho Harry Susanto; et al. (PLoS ONE, 2025)
Background Stroke is a major cause of death and disability, with prolonged hospitalization driving up healthcare costs. This study investigated factors influencing length of stay (LOS) in ischemic stroke patients at a leading Indonesian stroke center. Methods A retrospective cohort study was conducted on 2,804 ischemic stroke patients admitted in 2020. Univariable and multivariable zero truncated negative binomial regression analyses were performed using R Statistical Software (v4.5.1) to identify factors significantly associated with LOS. Results The study population had a mean age of 61.3 years (SD ± 11.4), with a predominance of male patients (63.5%). The average length of LOS was 5.1 days (SD ± 3.4). Several factors were significantly associated with LOS, including ward class (hospital ward class II: 0.91 IRR, 95% CI:0.86–0.97; VIP class: 0.87 IRR, 95%CI:0.79–0.96), payment method (private/co-share: 1.13 IRR, 95%CI:1.03–1.25; out-of-pocket: 1.19 IRR, 95%CI:1.09–1.30), and stroke severity (moderate: 1.16 IRR, 95%CI:1.11–1.21; severe: 1.56 IRR, 95%CI:1.44–1.69). Additionally, elevated blood pressure (0.85 IRR, 95%CI:0.73–0.98), stage 1 hypertension (0.90 IRR, 95%CI:0.82–0.99), diabetes mellitus (1.09 IRR, 95%CI:1.04–1.15), dyslipidemia (0.95 IRR, 95%CI:0.90–0.999), all at admission, and cardiovascular disease (CVD) history (1.24 IRR, 95%CI:1.19–1.29), hospital complications (1.99 IRR, 95%CI:1.87–2.12), and therapeutic interventions (1.38 IRR, 95%CI:1.29–1.48) were also significantly linked to LOS. A subgroup analysis showed that CVD history, hospital complications, and therapeutic interventions during hospitalization were significantly linked to the LOS across all levels of stroke severity. Conclusion CVD history, hospital complications, and therapeutic interventions significantly influenced LOS across stroke severities. Early intervention, complication prevention, and equitable care are essential to shorten hospitalization, reduce costs, and improve outcomes in Indonesian stroke patients.